2010
DOI: 10.1124/jpet.110.167601
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Gefitinib to the Brain Is Limited by P-glycoprotein (ABCB1) and Breast Cancer Resistance Protein (ABCG2)-Mediated Active Efflux

Abstract: Gefitinib is an orally active inhibitor of the epidermal growth factor receptor approved for use in patients with locally advanced or metastatic non-small cell lung cancer. It has also been evaluated in several clinical trials for treatment of brain tumors such as high-grade glioma. In this study, we investigated the influence of P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) on distribution of gefitinib to the central nervous system. In vitro studies conducted in MadinDarby canine kidney II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
195
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(211 citation statements)
references
References 38 publications
11
195
1
1
Order By: Relevance
“…This was first reported by de Vries et al (2007) and Polli et al (2009), who showed that P-gp and Bcrp work together to modulate the CNS penetration of topotecan (de Vries et al, 2007) and lapatinib (Polli et al, 2009), respectively. Furthermore, in our previous studies in Bcrp, P-gp, and P-gp/Bcrp knockout mice, we reported similar findings with dasatinib (Chen et al, 2009), gefitinib (Agarwal et al, 2010), and sorafenib (Agarwal et al, 2011b). These results showed that brain penetration of dual substrates increased disproportionally in the absence of both P-gp and Bcrp at the BBB.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…This was first reported by de Vries et al (2007) and Polli et al (2009), who showed that P-gp and Bcrp work together to modulate the CNS penetration of topotecan (de Vries et al, 2007) and lapatinib (Polli et al, 2009), respectively. Furthermore, in our previous studies in Bcrp, P-gp, and P-gp/Bcrp knockout mice, we reported similar findings with dasatinib (Chen et al, 2009), gefitinib (Agarwal et al, 2010), and sorafenib (Agarwal et al, 2011b). These results showed that brain penetration of dual substrates increased disproportionally in the absence of both P-gp and Bcrp at the BBB.…”
Section: Introductionsupporting
confidence: 68%
“…Brain distribution studies using these mice have shown that many drugs have limited CNS distribution due to P-gp-and/or Bcrp-mediated efflux (Lee et al, 2005;de Vries et al, 2007;Polli et al, 2009;Agarwal et al, 2010Agarwal et al, , 2011bKodaira et al, 2010;Tang et al, 2012). However, the finding that brain distribution of several dual P-gp and Bcrp substrates increased remarkably in mice deficient in both P-gp and Bcrp was unexpected, because there was no dramatic increase in their brain penetration in the single P-gp-or Bcrp-deficient mice.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Elacridar inhibited ABCG2 as well as ABCB1 and has been used in preclinical and clinical settings (38,39). Elacridar can also significantly increase plasma pharmacokinetics and brain distribution of several drugs, including dasatinib (40), gefitinib (41), and sunitinib (42). In this study, ABCB1 knockdown reduced the numbers of oncospheres and suppressed EMT features in EBC-1R cells.…”
Section: Discussionmentioning
confidence: 82%